Effects of extraction methods and storage conditions on histamine content in frozen tuna (Thunnus albacares) - Tran, Nhan Dung; Do, Tan Khang; Le, Anh Vu (CTU Journal of Innovation and Sustainable Development, 2016)
This study was undertaken to assess different extraction methods and the effects of times and temperatures on histamine produced in storage frozen tuna. The results showed that histamine in tuna samples could be efficiently extracted with perchloric acid 0.6 M and trichloroacetic acid 6%. The effective method for determining histamine concentration was benzoylation procedure. Tuna stored at 4oC resulted in higher histamine level (42.24 mg/kg) than tuna stored at 0oC (161.29 mg/kg) after 7 days of storage. Also, bacteria increased from 4.54 log10 cfu/g to 5.88 log10 cfu/g in the samples stored at 0°C, while for the samples stored at 4°C, an increase was shown dramatically in counts from 4.54 log10 cfu/g to 8.88 log10 cfu/g. These findings revealed that there was high correlation between storage conditions and histamine formation.